Financial Intelligence as a Moderator of the Relationship Between Financial Literacy and Financial Decision Making among Generation Z - Adinda Sakinah; Nurjannah Nurjannah; Hikmayani Subur (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
The growing use of digital financial services has made financial decision-making increasingly complex for young people, especially Generation Z. Although this generation is familiar with financial technology, easy access to digital financial products does not always lead to careful, rational, and responsible financial choices. This study examines the influence of financial literacy on financial decision-making and investigates whether financial intelligence strengthens this relationship. A quantitative explanatory design was applied in this research. The respondents consisted of 100 Generation Z students from the Faculty of Economics and Business, Universitas Negeri Makassar, selected through purposive sampling. Data were obtained using a structured questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. The findings reveal that financial literacy positively and significantly influences financial decision-making. Financial intelligence also shows a positive and significant effect, with a stronger contribution to students’ financial decision-making. In addition, financial intelligence significantly moderates the relationship between financial literacy and financial decision-making. These results suggest that financial knowledge needs to be supported by the ability to apply such knowledge in real financial situations. Therefore, Generation Z students require not only financial literacy, but also financial intelligence to control impulses, assess risks, and make responsible financial decisions in the digital financial environment.